Strategi Pengelolaan Usahatani Cabai Rawit dalam Meningkatkan Pendapatan Masyarakat di Matur Kabupaten Agam - Adelia Sonia Fitri; Iizmuddin Iizmuddin (Lembaga Yasin AlSys, 2026)
Although strategies for managing cayenne pepper farming have received attention in various studies, studies that specifically discuss the management of cayenne pepper farming in an effort to increase community income at the local level, particularly in Matur Subdistrict, remain limited. This study aims to identify and analyze the management conditions of cayenne pepper farming, the constraints faced by farmers, and the strategies that can be implemented to increase community income. This study employed a qualitative approach with a descriptive design, involving eight informants selected through purposive sampling. Data were collected through observation, interviews, and documentation, and were then analyzed through the stages of data reduction, data display, and conclusion drawing. The results showed that the management of cayenne pepper farming had applied management functions consisting of planning, organizing, implementation, and supervision. These strategies were able to increase farmers’ income, although it remained unstable due to price fluctuations, weather conditions, pest and disease attacks, and limited capital. In addition, farmers tended to sell their harvests to middlemen because of easier access and market certainty, even though the prices received were lower. Crop diversification also became a strategy used by farmers to reduce risk and maintain income stability. These findings contribute to the development of farm management theory while broadening understanding of small-scale agricultural management strategies. This study concludes that effective farm management and appropriate marketing strategies are important factors in increasing farmers’ income, so the government and related parties need to strengthen access to market information, capital, and technical assistance.